Analysis of Special Allocation Fund (DAK) Budget Absorption in Stunting Reduction Efforts: A Case Study of South Buton Regency Health Office - Nofianti, Sri; Pono, Maat; Sundari, Sri (Pancasila International Journal of Applied Social Science, 2023)
Stunting, a condition of chronic malnutrition leading to impaired growth in children, poses a significant global public health challenge with far-reaching consequences. Effective intervention, including adequate budget allocation, is essential to address this issue. The Indonesian government has allocated funds through the Special Allocation Fund (DAK) program to support stunting reduction efforts, including those in South Buton Regency. However, the level of budget absorption in South Buton Regency requires evaluation, as low absorption can impede program effectiveness. This research employs a qualitative approach with descriptive analysis to assess DAK budget absorption and influencing factors. The findings reveal suboptimal absorption rates, with factors such as inadequate planning, administrative hurdles, allocation mismatches, and limited human resource capacity impacting absorption. Recommendations for improvement include refined planning, streamlined bureaucracy, capacity building, and rigorous monitoring and evaluation. This research holds implications for optimizing budget utilization and improving stunting reduction program implementation in South Buton Regency, with broader relevance for similar challenges in other regions. It contributes to the understanding of effective strategies for addressing stunting and underscores the importance of appropriate budget allocation and absorption in supporting public health initiatives.